Characterization of Histone H3 Lysine 4 and 36 Tri-methylation in Brassica rapa L. - Mehraj, Hasan; Takahashi, Satoshi; Miyaji, Naomi; Akter, Ayasha; Suzuki, Yutaka; Seki, Motoaki; Dennis, Elizabeth S.; Fujimoto, Ryo (Frontiers in Plant Science, 2021)
Covalent modifications of histone proteins act as epigenetic regulators of gene expression. We report the distribution of two active histone marks (H3K4me3 and H3K36me3) in 14-day leaves in two lines of Brassica rapa L. by chromatin immunoprecipitation sequencing. Both lines were enriched with H3K4me3 and H3K36me3 marks at the transcription start site, and the transcription level of a gene was associated with the level of H3K4me3 and H3K36me3. H3K4me3 and H3K36me3-marked genes showed low tissue specific gene expression and genes with both H3K4me3 and H3K36me3 had a high level of expression and were constitutively expressed. Bivalent active and repressive histone modifications such as H3K4me3 and H3K27me3 marks or antagonistic co-existence of H3K36me3 and H3K27me3 marks were observed in some genes. Expression may be susceptible to changes by abiotic and biotic stress in genes having both H3K4me3 and H3K27me3 marks. We showed the presence of H3K36me3 marks was associated with different gene expression levels or tissue specificity between paralogous paired genes, suggesting that H3K36me3 might be involved in subfunctionalization of the subgenomes.